Mechanism of Growth Regulation of Yeast Involving Hydrogen Sulfide From S-Propargyl-Cysteine Catalyzed by Cystathionine-γ-Lyase - Gu, Zhongkai; Sun, Yufan; Wu, Feizhen; Wu, Xiaomo (Frontiers in Microbiology, 2021)
Pathogenic fungi are recognized as a progressive threat to humans, particularly those with the immunocompromised condition. The growth of fungi is controlled by several factors, one of which is signaling molecules, such as hydrogen sulfide (H2S), which was traditionally regarded as a toxic gas without physiological function. However, recent studies have revealed that H2S is produced enzymatically and endogenously in several species, where it serves as a gaseous signaling molecule performing a variety of critical biological functions. However, the influence of this endogenous H2S on the biological activities occurring within the pathogenic fungi, such as transcriptomic and phenotypic alternations, has not been elucidated so far. Therefore, the present study was aimed to decipher this concern by utilizing S-propargyl-cysteine (SPRC) as a novel and stable donor of H2S and Saccharomyces cerevisiae as a fungal model. The results revealed that the yeast could produce H2S by catabolizing SPRC, which facilitated the growth of the yeast cells. This implies that the additional intracellularly generated H2S is generated primarily from the enhanced sulfur-amino-acid-biosynthesis pathways and serves to increase the growth rate of the yeast, and presumably the growth of the other fungi as well. In addition, by deciphering the implicated pathways and analyzing the in vitro enzymatic activities, cystathionine-γ-lyase (CYS3) was identified as the enzyme responsible for catabolizing SPRC into H2S in the yeast, which suggested that cystathionine-γ-lyase might play a significant role in the regulation of H2S-related transcriptomic and phenotypic alternations occurring in yeast. These findings provide important information regarding the mechanism underlying the influence of the gaseous signaling molecules such as H2S on fungal growth. In addition, the findings provide a better insight to the in vivo metabolism of H2S-related drugs, which would be useful for the future development of anti-fungal drugs.